Nonlysosomal, pre-Golgi degradation of unassembled asialoglycoprotein receptor subunits: a TLCK- and TPCK-sensitive cleavage within the ER (The Rockefeller University Press, 1991)
The human asialoglycoprotein receptor subunit H2a is cotranslationally inserted into the ER membrane. When expressed together with subunit H1 in mouse fibroblasts part forms a hetero-oligomer that is transported to the cell surface, but when expressed alone it is all rapidly degraded. Degradation is insensitive to lysosomotropic agents and the undegraded precursor is last detected in the ER region of the cell. Small amounts of an intermediate 35-kD degradation product can be detected (Amara, J. F., G. Lederkremer, and H. F. Lodish. 1989. J. Cell Biol. 109:3315). We show here that the oligosaccharides on both precursor H2a and the 35-kD fragment are Man6-9GlcNAc2, structures typically found in pre-Golgi compartments. Subcellular fractionation shows that the intermediate degradation product does not cofractionate with the lysosomal enzyme beta-galactosidase, but is found in a part of the ER that contains ribosomes. Thus the intermediate degradation product is localized in the ER, indicating that the initial degradation event does take place in the ER. All degradation of H2a, including the initial endoproteolytic cleavage generating the 35-kD intermediate, is blocked by the protease inhibitors N-tosyl-L-lysine chloromethyl ketone and N-tosyl-L-phenylalanine chloromethyl ketone. These drugs do not inhibit ER-to-Golgi transport of H1. Depleting the cells of ATP or inhibiting protein synthesis allows the initial endoproteolytic cleavage to occur, but blocks further degradation of the 35-kD intermediate; thus we can convert all cellular H2 into the 35-kD intermediate. Approximately 50% of H2b, a splicing variant differing from H2a by a five amino acid deletion, can be transported to the cell surface, and the rest appears to be degraded by the same pathway as H2a, both when expressed alone in fibroblasts and together with H1 in HepG2 cells. Addition of N-tosyl-L-lysine chloromethyl ketone or N- tosyl-L-phenylalanine chloromethyl ketone blocks degradation of the approximately 50% that is not transported, but does not affect the fraction of H2b that moves to the Golgi region. Thus, a protein destined for degradation will not be transported to the Golgi region if degradation is inhibited.